The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s40292-016-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness in Aortic Stenosis: Relationship with Severity and Echocardiographic Procedures Response

Abstract: In patients undergoing procedures for AS, PWV is correlated with transvalvular gradient and, in TAVI subjects, is able to predict the echocardiographic response. Baseline evaluation of PWV in patients candidates to TAVI can help the selection of subjects, even if larger and longer studies are needed before definitive conclusion can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…Bruschi et al reported elevated cfPWV in patients with AS undergoing AVR (surgical or transcatheter). 22 The cfPWV increased with increasing aortic valve MPG. In another study using invasive measurement of aortic stiffness, aorto-femoral PWV strongly correlated with MPG and the extent of aortic valve calcification.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bruschi et al reported elevated cfPWV in patients with AS undergoing AVR (surgical or transcatheter). 22 The cfPWV increased with increasing aortic valve MPG. In another study using invasive measurement of aortic stiffness, aorto-femoral PWV strongly correlated with MPG and the extent of aortic valve calcification.…”
Section: Discussionmentioning
confidence: 95%
“…Several different parameters have been used to quantify LV afterload in patients with severe AS. 18 , 20 , 21 , 22 , 34 , 37 The most commonly used among these are ZVa, effective arterial elastance and total arterial compliance. It has been demonstrated that the patients with low-flow, severe AS have increased ZVa and effective arterial elastance whereas total arterial compliance is reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study compared the effects of both SAVR and TAVI on aortic stiffness and found that treatment of severe AoS by SAVR, but not with TAVI, was associated with an increase in aortic stiffness at 6 months 25. Conversely, other authors found no significant change in aortic stiffness after replacing the aortic valve in both SAVR and TAVI patients 12…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated changes in systolic blood pressure (SBP) and diastolic blood pressure (DBP) as well as aortic stiffness after surgical aortic valve replacement (SAVR),912 and one study observed improvement of aortic distensibility 11. At present, there is little and conflicting information on the short-term aortic functional properties after transcatheter aortic valve implantation (TAVI) 1214. The objective of this study was to assess the effect of TAVI on aortic stiffness and blood pressure levels shortly after TAVI.…”
Section: Introductionmentioning
confidence: 99%